2005
DOI: 10.1007/978-3-540-31987-0_14
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of an Electronic Voting Protocol in the Applied Pi Calculus

Abstract: Abstract. Electronic voting promises the possibility of a convenient, efficient and secure facility for recording and tallying votes in an election. Recently highlighted inadequacies of implemented systems have demonstrated the importance of formally verifying the underlying voting protocols. The applied pi calculus is a formalism for modelling such protocols, and allows us to verify properties by using automatic tools, and to rely on manual proof techniques for cases that automatic tools are unable to handle.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
142
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 146 publications
(145 citation statements)
references
References 16 publications
2
142
0
1
Order By: Relevance
“…In [12], it is shown that this protocol provides fairness, eligibility and privacy. However, the proof of privacy given in [12] is manual: ProVerif is unable to prove it directly.…”
Section: E-voting Protocol Due To Fujioka Et Almentioning
confidence: 99%
See 4 more Smart Citations
“…In [12], it is shown that this protocol provides fairness, eligibility and privacy. However, the proof of privacy given in [12] is manual: ProVerif is unable to prove it directly.…”
Section: E-voting Protocol Due To Fujioka Et Almentioning
confidence: 99%
“…In the context of voting protocols, the definition of privacy is rather subtle. We recall the definition of privacy for electronic voting protocols given in [12]. A voting protocol guarantees ballot secrecy (privacy) whenever a process where Alice votes for candidate v 1 and Bob votes for candidate v 2 is observationally equivalent to a process where their votes are swapped, i.e.…”
Section: Modelling Privacy In Applied Pimentioning
confidence: 99%
See 3 more Smart Citations